Cognitive differences in the perception of metaphorical images among Taiwanese high school students - Chia-Rong Lee; Chun-Yi Lee (Cogent Arts & Humanities)
Many images used in media and advertising employ visual metaphors that provide enjoyment and storytelling. This study employed an image perception questionnaire to evaluate high school students’ image preferences. The results revealed that among the adjectives provided by the researcher, high school students exhibited higher preferences for describing images as creative, symbolic, cultural, artistic, contrasting, serious, exaggerated, and rational imagery. According to the independent sample t-test results, a pronounced gender difference existed in the preference of selection from the ‘Conservative–Creative’ adjective pair to describe images. Additionally, male and female students displayed higher preferences for describing fusion metaphorical images as ‘natural’ and ‘cultural’, respectively. The preferences of students of different genders for metaphorical images were considerably influenced by the conservative, creative, natural, or cultural elements of the images. According to the results of the chi-square test of independence and phi correlation coefficient test, gender exhibited a significant but low correlation with students’ preferences for juxtaposed and replacement metaphorical images. The findings of this study can provide valuable insights for art educators to gain a deeper understanding of gender differences in students’ image assessments and preferences when viewing images, helping them select appropriate visual teaching materials.